Can information be locked up? Informed trading ahead of macro-news announcements - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2016)
Government agencies routinely allow pre-release access to information to accredited news agencies under embargo agreements. Using high-frequency data, we find evidence consistent with informed trading during embargoes of Federal Open Market Committee (FOMC) scheduled announcements. The E-mini Standard & Poor’s 500 futures’ abnormal order imbalances are in the direction of subsequent policy surprises and contain information that predicts the market reaction to the policy announcements. The estimated informed trades’ profits are arguably large. Notably, we find no evidence of informed trading prior to the start of FOMC news embargoes or during lockups ahead of nonfarm payroll, US Producer Price Index, and gross domestic product data releases.